Answer:
[tex]\frac{-1+/-3\sqrt{2} }{2}[/tex] where a = 1, b = 1,and c=-4
Step-by-step explanation:
To solve, use the quadratic formula. Using the quadratic formula, requires the standard form [tex]ax^2+bx+c[/tex] Here a = 1, b = 1, and c = -4.
The quadratic formula is [tex]x=\frac{-b+/-\sqrt{b^2-4ac} }{2a}[/tex].
Substitute and you'll have:
[tex]x=\frac{-b+/-\sqrt{b^2-4ac} }{2a} =\frac{-1+/-\sqrt{1^2-4(1)(-4)} }{2(1)}=\frac{-1+/-\sqrt{1+17} }{2)}[/tex]
[tex]\frac{-1+/-\sqrt{18} }{2}=\frac{-1+/-3\sqrt{2} }{2}[/tex]